2021
DOI: 10.19126/suje.840070
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Prosocial and Antisocial Behaviors and Personality Traits in Team Athletes

Abstract: The aim of this study was to investigate the relationships between personality traits and prosocial and antisocial behaviors displayed in team athletes. In this respect, the data was collected from a total of 445 (61 females and 384 males) participants engaged in team sports. The relational screening model was used in the study. The Prosocial and Antisocial Behavior in Sports Scale, Five Factor Personality Inventory and Personal Information Form prepared by the researcher were used to collect data. Descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In this respect, it was found that competitors obtained high results in the areas of extraversion, openness, willingness and contentiousness and low results in the area of neuroticism [ 48 ]. A low level of neuroticism among athletes was also described in other studies conducted in a group of competitive athletes, including those training in team sports [ 64 , 65 ], and also among Polish athletes [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 63%
“…In this respect, it was found that competitors obtained high results in the areas of extraversion, openness, willingness and contentiousness and low results in the area of neuroticism [ 48 ]. A low level of neuroticism among athletes was also described in other studies conducted in a group of competitive athletes, including those training in team sports [ 64 , 65 ], and also among Polish athletes [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 63%
“…It should be noted, however, that the authors’ intention was only performing a limited analysis of the athletes’ personality traits, to an extent constituting a background for the assessment of psychological determinants of nutritional behaviours. Nonetheless, it may be concluded that in other papers on the personality of athletes, different trends were shown, while all these studies allow confirmation of a low level of neuroticism among competitive athletes, including those performing team sports [ 45 , 46 ], and also among Polish athletes [ 47 ], especially those at a championship level [ 48 , 49 ]. The tendency towards low levels of neuroticism among athletes is important for interpreting its predictive role in the quality of athletes’ eating behaviours.…”
Section: Discussionmentioning
confidence: 98%
“…Athletes practicing team sports (football, handball and water polo) obtained the highest scores in terms of Openness to Experience , Agreeableness and Extraversion , but lower values in terms of Conscientiousness , and the lowest with regard to Neuroticism [ 52 ]. Similarly, in the next group of athletes performing team sports, the highest levels of Openness to Experience and the lowest of Neuroticism were demonstrated [ 53 ]. Therefore, it may be concluded that, despite the different configuration of features, the trend occurring in the majority of studies conducted among professional athletes is the lowest intensity of the Neuroticism dimension among the features included in the Costa and McCrae five-factor model.…”
Section: Discussionmentioning
confidence: 99%